1986
DOI: 10.1073/pnas.83.22.8487
|View full text |Cite
|
Sign up to set email alerts
|

Molecular models for the putative dimer of sea lamprey hemoglobin.

Abstract: The known structures for the tetramers of mammalian and clam hemoglobins provide a point of departure for the modeling of putative dimers of lamprey hemoglobin. The association of subunits is dissimilar for the clam and mammalian tetramers; the superposition of the molecular model for lamprey methemoglobin onto the mammalian and clam tetramers gives five distinct dimers. After energy minimization of the interface regions of the five models, three models afford promising interactions between side chains. One mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
(20 reference statements)
0
5
1
Order By: Relevance
“…The low metabolic rate of hagfish does not seem to require a highly cooperative oxygen carrier, and our structures confirm that F1 is unable to form monomer-monomer interactions of the kind found in higher vertebrate Hbs. The long N-terminal extension and the deletion between the G and H helices make both ␣ 1 ␤ 1 -and ␣ 1 ␤ 2 -type interactions impossible (4). It has been suggested that hagfish Hbs represent an intermediate between invertebrate and vertebrate Hbs (47), but we see no evidence of direct heme-heme interaction as found in the Hb of the clam S. inaequivalvis (27).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The low metabolic rate of hagfish does not seem to require a highly cooperative oxygen carrier, and our structures confirm that F1 is unable to form monomer-monomer interactions of the kind found in higher vertebrate Hbs. The long N-terminal extension and the deletion between the G and H helices make both ␣ 1 ␤ 1 -and ␣ 1 ␤ 2 -type interactions impossible (4). It has been suggested that hagfish Hbs represent an intermediate between invertebrate and vertebrate Hbs (47), but we see no evidence of direct heme-heme interaction as found in the Hb of the clam S. inaequivalvis (27).…”
Section: Discussioncontrasting
confidence: 48%
“…In the case of lamprey Hbs, the dissociation of ligands promotes oligomerization of the protein. On the basis of a monomer structure of the cyanidebound ferric form, Honzatko and Hendrickson (4) suggested that the subunit interfaces of the deoxy-Hb oligomer were the same as the ␣ 1 ␤ 2 interface of the ␣ 2 ␤ 2 tetramer. Recently, however, Heaslet and Royer (5) solved the x-ray structure of lamprey deoxy-Hb and found a dimer with an interface between the E helix and AB corner, totally different from any of the interfaces in the ␣ 2 ␤ 2 tetramer.…”
mentioning
confidence: 99%
“…The formation of heteromultimers composed of unlike subunits appears superficially similar to the α 2 β 2 heterotetramers of most gnathostomes, but the oxygenation-linked transition in quaternary structure is completely different. The intersubunit contacts of heterotetrameric gnathostome Hbs primarily involve the C, G, and H helices of the globin chain subunits (51), whereas the contact surfaces of the deoxygenated, homodimeric cyclostome Hbs involve the E helix and the AB corner, such that the heme groups are in almost direct contact (52)(53)(54)(55). The heme-heme interactions of cyclostome Hbs are intriguingly similar to those of the homodimer of Cygb (23,38,39,56,57), an observation that makes sense in light of our inferred phylogenetic relationship between these two globin proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of sequence analysis, Li and Riggs proposed that the dimer would form an interface similar to the α 1 β 2 interface of human hemoglobin [13]. Additionally, Honzatko and Hendrickson have proposed three possible dimer assemblages based on those observed in human and Scapharca (mollusc) hemoglobins [14].…”
Section: Introductionmentioning
confidence: 99%